THE PRINCIPLE OF OPERATION OF THE PERCEPTRON AND ITS APPLICATIONS. (Modern education and development, 2025)
The article presents the algorithm of operation of the perceptron, the necessary conditions and technical aspects for its correct operation. It also considers its application in various fields such as machine learning, classification, face recognition, and handwritten digit recognition. The perceptron is the basis for the development of modern artificial intelligence systems and is important as one of the main elements of deep learning.